Optimization of Ultrasonicated Membrane Anaerobic System for Sewage Sludge Treatment Using Response Surface Methodology (RSM) - Mazza, A. S.; Nour, A. H.; Said, N.; N., Zainol; Mohamed, B. S. (eSAT Publishing House Pvt. Ltd., 2014)
Ultrasonicated Membrane Anaerobic System UMAS was successfully used for sewage sludge treatment and biogas production. Central Composite Design and Response Surface Methodology were used to determine the optimum conditions in which UMAS produce a maximum content of methane in the biogas produced. The effects of three variables namely pH, chemical oxygen demand (COD) and organic loading rate (OLR) on methane content were evaluated individually and interactively. The optimum conditions obtained were pH 7.74, COD 1061.06 Mg/l and OLR 0.90 kg/m3d. The predicted maximum percentage of methane was 89.72 % and confirmed close to RSM result.